Yttria stabilized zirconia: innovative approach for improving the performance of additively manufactured denture resins - Hadeel F Majeed; Thekra I Hamad; Zeina Al-Salihi (Journal of Baghdad College of Dentistry, 2025)
Background: The development of additive manufacturing technology facilitated the advancement of 3D-printed denture resins, though these materials show limitations in their physical and mechanical properties. Aims: This study investigated the effects of adding yttria-stabilized zirconia nanoparticles to 3D-printed denture resin to improve its performance at weights of 1% and 3%. The focus was on impact strength, surface hardness, and roughness. Materials and methods: 90 specimens of 3D-printed acrylic were divided into three groups, then further divided each group into three subgroups based on the results of each test. Charpy's Impact Strength Tester was used to evaluate impact strength. Surface characteristics were assessed by Vickers microhardness (HV) tester (microhardness) and non-contact profilometer (roughness). Fourier transform infrared spectroscopy (FTIR) was utilized for the chemical analysis. The experimentation's data guided the statistical analysis, which included descriptive statistics, analysis of variance (ANOVA), and multiple comparison tests based on the significance of each test's outcomes. Results: The results verified that adding 1 wt.% and 3 wt.% YSZ NPs to the 3D-printed denture resin significantly enhanced its mechanical and surface characteristics (p < 0.05) compared to unmodified resin. Conclusion: The addition of YSZ NPs enhanced the impact strength, surface hardness, and roughness. FTIR analysis showed that the polymer and YSZ nanoparticles did not interact chemically. This suggests that a new 3D-printed nanocomposite denture base with better performance is possible.